THE PRINCIPLE OF PRESUMPTION OF INNOCENCE AND PROSECUTION POLICY - Haryanto, M . (Faculty of Law, Universitas Sebelas Maret, 2016)
The issue IF this article is to be addressed in this article is the incompatibility between the prosecution policy issued by the Supreme Prosecutor’s Office of the Republic of Indonesia and the principle of presumption of innocence. This article finds that the General Attorney’s Office disregards the principle of presumption of innocence recognized by the Criminal Procedural Law by issuing General Attorney Directive on Criminal Prosecution and General Attorney Notice dispatched to the Head of High Prosecutor’s Office which denied the Prosecutor’s authority to request for acquittal in a criminal litigation. To solve this issue, the author argues that in a case where the evidence did not support the prosecution in relation with the existence of the crime or the perpetrator who is not the convicted, the Prosecutor should embrace the principle of presumption of innocence and consequently request for acquittal of the accused or convicted.